2020
DOI: 10.1096/fj.202001106rrr
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin 1‐induced exosomal proteins attenuate hypoxia‐induced paraptosis in corneal epithelial cells and promote wound healing

Abstract: Thrombospondin‐1 (TSP1) is involved in corneal wound healing caused by chemical injury. Herein, we examined the effects of TSP1 on hypoxia‐induced damages and wound‐healing activity in human corneal epithelial (HCE) cells. Exosomal protein expression was determined using liquid chromatography‐tandem mass spectrometry, and HCE cell migration and motility were examined through wound‐healing assay and time‐lapse microscopy. Reestablishment of cell junctions by TSP1 was assessed through confocal microscopy and 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 44 publications
0
4
0
2
Order By: Relevance
“…More recently, our laboratory found that epithelial-EVs released by corneal epithelial cells encapsulate provision matrix proteins that triggers corneal fibroblast to myofibroblast differentiation, while also contributing to elevated contractility, proliferation, and migration [ 20 ]. In a similar study, it was shown corneal epithelial-EVs have the capacity to influence the transdifferentiation of human conjunctival and corneal epithelial cells [ 124 ], or EVs pre-treated with thrombospondin-1 promoted tissue remodeling and repair [ 125 ]. More recently, our study examined the paracrine crosstalk from the corneal stromal (keratocytes, fibroblasts, and myofibroblasts) EVs and how they influence corneal epithelial wound healing [ 23 ].…”
Section: What Roles Do Extracellular Vesicles Play In Corneal Fibrosi...mentioning
confidence: 99%
“…More recently, our laboratory found that epithelial-EVs released by corneal epithelial cells encapsulate provision matrix proteins that triggers corneal fibroblast to myofibroblast differentiation, while also contributing to elevated contractility, proliferation, and migration [ 20 ]. In a similar study, it was shown corneal epithelial-EVs have the capacity to influence the transdifferentiation of human conjunctival and corneal epithelial cells [ 124 ], or EVs pre-treated with thrombospondin-1 promoted tissue remodeling and repair [ 125 ]. More recently, our study examined the paracrine crosstalk from the corneal stromal (keratocytes, fibroblasts, and myofibroblasts) EVs and how they influence corneal epithelial wound healing [ 23 ].…”
Section: What Roles Do Extracellular Vesicles Play In Corneal Fibrosi...mentioning
confidence: 99%
“…They were subjected to the same hypoxic stress encountered in corneal wound healing. Exosomes with TSP-1 as a cargo protein decrease paraptosis (apoptosis caused by hypoxic conditions) [ 57 ]. EVs derived from human placenta mesenchymal stem cells were used to treat alkali-burned mouse corneas.…”
Section: Regeneration Of Scarless Corneamentioning
confidence: 99%
“…[ 290 ]. Another study reported that thrombospondin-1 ameliorated hypoxia-induced paraptosis and promoted wound healing and remodeling by regulating exosomal protein expression in human corneal epithelial cells [ 291 ]. However, exosomes derived from antigen presenting cells, such as dendritic cells and B lymphocytes, can carry major histocompatibility complex class I and II molecules on the surface, which can induce stronger antigen-specific immune responses [ 292 ].…”
Section: Therapy Of Lscdmentioning
confidence: 99%